MAVS signaling of long-lived brain-resident myeloid cells is needed during viral encephalitis to adjust the transcriptome of CNS infiltrating CD8+ T cells - Andreas Pavlou; Luca Ghita; Felix Mulenge; Inken Waltl; Olivia Luise Gern; Pia-Katharina Larsen; Bibiana Costa; Veronica Duran; Lena Mareike Busker; Shelly J. Robertson; Yvonne Lueder; Stephan Halle; et al. (Journal of Neuroinflammation)
Abstract Neurotropic viruses like vesicular stomatitis virus (VSV) can infect the central nervous system (CNS) through the olfactory route. Following intranasal instillation, VSV moves along the axons of olfactory sensory neurons to the olfactory bulb. While within the olfactory bulb the spread of the virus is controlled by microglia activation and the recruitment of peripheral leukocytes, some of the underlying mechanisms remain unknown. To investigate these mechanisms, we used mice with conditional deletions of the mitochondrial antiviral-signaling protein (MAVS), an adaptor for RIG-I-like receptor (RLR) signaling. By selectively deleting MAVS in neurons, astrocytes, or long-lived myeloid cells, we discovered that RLR signaling specifically within brain-resident myeloid cells is crucial for protection against the virus. Infected mice with a MAVS deletion in these myeloid cells showed normal myeloid cell and leukocyte infiltration into the brain. However, the P2RY12+ microglia showed aberrant expression of genes involved in antigen cross-presentation. Furthermore, flow cytometry experiments revealed diminished MHC class I expression on MAVS deficient microglia. Moreover, CNS infiltrating CD8+ T cells had dysfunctional transcriptional profiles. Therefore, our findings indicate that during viral CNS infection, MAVS signaling in brain-resident myeloid cells, presumably microglia, is essential for antigen cross-presentation and the relicensing of protective, infiltrating CD8+ T cells.